Matlab simulink for modelling facts devices application in power transmission network / Mohd Fadly Razak - Razak, Mohd Fadly (2009)
This project focuses in the modeling of FACTS (Flexible AC Transmission System) device application in power transmission network utilizing Matlab Simulink software. The designed was tested on IEEE 9 busbar system using Matlab Simulink.